IoT enabled integrated system for green energy into smart cities. (August 2021) - Zhang, Xiangdong; Manogaran, Gunasekaran; Muthu, BalaAnand
Abstract: With the substantial social and environmental change at the global level, increasing numbers of cities worldwide have been directed their infrastructure strategies towards sustainable mobility policies, building stock updating energy, increasing renewable energy production, improving waste management, and implementing ICT infrastructures. A significantly greater part of heat and electricity sources and the high level of integration of households and businesses in industry and utilities is needed in smart city energy systems. This article provides a comprehensive methodology to plan and evaluate the creation of smart power systems that lead to complex networks of energy supply technologies using diverse on-site and off-site resources. In this paper, the Internet of Things based Smart Green Energy (IoT-SGE) has been proposed for Smart Cities. With the implementation of IoT, smart cities can exquisitely control energy through pervasive monitoring and secure communications. This article focuses on designing an IoT-based smart energy management system enabled by deep reinforcement learning. The finding outcomes show that IoT sensors to detect energy consumption, predict the energy demand in smart cities and cost-saving.